Comminuted intraarticular calcaneal fractures: Multiplanar VA locked plating and interlocked nailing incorporate longitudinal strut and provide superior stability – a biomechanical cadaveric study. Issue 10 (October 2022) - Stefanov, A.; Ivanov, S.; Zderic, I.; Baltov, A.; Rashkov, M.; Gehweiler, D.; Richards, G.; Gueorguiev, B.; Enchev, D.
Highlights: Multiplanar variable-angle locked plating and interlocked nailing, both in combination with separate cannulated screws, incorporate longitudinal metallic strut and provide superior stability of comminuted intraarticular calcaneal fractures. The overall construct stability in comminuted intraarticular calcaneal fractures benefits from multiplanar buttressing of the posterior facet. The calcaneal region at the critical angle of Gissane is vulnerable to fail first in comminuted fractures involving the posterior facet and the articular surface of the calcaneocuboid joint. Abstract: Treatment of comminuted intraarticular calcaneal fractures remains controversial and challenging. The aim of this study was to investigate the biomechanical performance of three different methods for fixation of such fractures. Comminuted calcaneal fractures, including Sanders III AB fracture of the posterior facet and Kinner II B fracture of the calcaneocuboid joint (CCJ) articular calcaneal surface, were created in 18 human cadaveric lower legs by osteotomizing. The ankle joint, medial soft tissues and midtarsal bones along with their ligaments were preserved. The specimens were randomized to three groups for fixation with either (1) 2.7 mm variable-angle locking lateral calcaneal plate (Group 1), (2) 2.7 mm variable-angle locking anterolateral calcaneal plate in combination with one 4.5 mm and one 6.5 mm cannulated screws (Group 2), or (3) interlocking calcaneal nail with 3.5 mm screws in combination with three separate 4.0 mm cannulated screws (Group 3). All specimens were biomechanically tested to failure under axial loading in midstance foot position. Each test commenced with a quasi-static compression ramp from 50 to 200 N, followed by progressively increasing cyclic loading at 2 Hz. Starting from 200 N, the peak load of each cycle increased at a rate of 0.2 N/cycle. Interfragmentary movements were captured by motion tracking. In addition, mediolateral X-rays were taken every 250 cycles with a triggered C-arm. Böhler angle after 5000 cycles (1200 N peak load) increased significantly more in Group 1 compared to both other groups (P ≤ 0.020). Varus deformation of 10° between the calcaneal tuberosity and the lateral calcaneal fragments was reached at significantly lower number of cycles in Group 1 compared the other groups (P ≤ 0.017). Both cycles to 10° plantar gapping between the anterior process and the calcaneal tuberosity fragments, and 2 mm displacement at the CCJ articular calcaneal surface revealed no significant differences among the groups (P ≥ 0.773). From a biomechanical perspective, treatment of comminuted intraarticular calcaneal fractures using anterolateral variable-angle locking plate with additional longitudinal screws or interlocked nail in combination with separate transversal screws provides superior stability as opposed to lateral variable-angle locked plating only.